Pengaruh Gaya Kepemimpinan dan Insentif Terhadap Kinerja Guru di Sekolah Menengah Kejuruan Hidayatul Mubtadien Sampang - Achmad Imam (Triwikrama: Jurnal Ilmu Sosial, 2024)
This study aims to determine the effect of leadership style and incentives on Teacher Performance in Schools Middle Vocational Hidayatul Sampang. Data obtained from distributing questionnaires to Teacher Performance in Schools Middle Vocational Hidayatul Sampang. This study uses data collection techniques, namely saturated sampling, where all members of the population used are all Teacher in Schools Middle Vocational Hidayatul Sampang. The data analysis technique used in this study is the classical assumption test. Data analysis uses multiple linear regression to obtain a comprehensive picture of the relationship between variables. The results of the study show that leadership style and work motivation have a positive and significant effect on Teacher Performance in Schools Middle Vocational Hidayatul Sampang